Librarians, historians, and new opportunities for discourse a guide for Clio's helpers - Kitchens, Joel D. (Santa Barbara, Calif. Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2012)
This book stimulates informed dialogue between librarians and historians regarding the changing nature of history and the resultant needs for a wider variety of collections and library services, including inter-library loan, library instruction, outreach, and reference.
Includes bibliographical references (pages 113-117) and index.
Keywords: Historical libraries; Libraries -- Special collections -- History; History -- Bibliography -- Methodology; Library orientation for history students; Historiography; History -- Research; History -- Methodology